Improvement of climacteric symptoms with a novel sublingual product containing trans-resveratrol - Milia, R (Progress in Nutrition, 2015)
Objectives: To assess the improvement of climacteric symptoms, especially hot flushes, evaluated analyzing the total score of Menopause Rating Scale, after supplementation with a new sublingual spray formulation of resveratrol (Talitha® PH&T SpA) able to bypass gastro-enteric tract entering directly the systemic circulation. Materials and Methods: 30 women with symptoms suggestive of climacteric syndrome present for at least one month, with or without associated amenorrhea, and evaluated according to the standardized Menopause Rating Scale (MRS) were enrolled in an open, uncontrolled study. The Sublingual Spray was administered: 4 puffs 2 times/day for 3 months. Results: Menopause Rating Scale total score: this reduction was statistically significant at 0.01 level. Hot flushes mean score: this reduction was statistically significant at the 0.01 level. MRS Single items total score: the following items showed a statistically significant reduction (p<0.05): heart discomfort; sleep problems; depression mood; irritability; physical and mental discomfort; joint and muscular discomfort. Moreover no patient experienced any side effects and compliance was optimal. Discussion: resveratrol is a powerful phytoestrogen that can be used as an alternative to hormone replacement therapy. The novel product is formulated as a sublingual spray emulsion, by which resveratrol is rapidly absorbed through the sublingual mucosa reaching the systemic circulation, without being metabolized and thus inactivated by the liver. Conclusions: The results of this study show that the novel sublingual product produces a statistically significant reduction of the main symptoms associated with menopause when measured with a validated method.